Contribution of bedrock structures to the bedrock surface topography and groundwater flow systems within deep glaciofluvial aquifers in Kurikka, Western Finland - Ruuska Eemi; Skyttä Pietari; Putkinen Niko; Valjus Tuire (WILEY, 2025)
One of the key challenges related to glaciofluvial aquifers is understanding how the underlying bedrock structures and the associated bedrock surface topography contributed to the deposition of the glaciofluvial sediments and the generation of groundwater flow pathways. In this study from Western Finland, we present a new digital elevation model of the Precambrian crystalline bedrock surface buried up to 100 m beneath the glaciofluvial sediments along the Kurikka depression. We link bedrock topography to structural anisotropy using additional data from rock outcrops, boreholes and gravity data. Brittle deformation zones are seen in the bedrock-digital elevation model (DEM) as sharp breaks in the rock surface. These vertical fracture zones contributed to the development of interlinked elongate bedrock depressions and delimit rock blocks with different elevations. A narrow, zigzagging trench, with a stepped floor, follows WNW-ESE and NE-SW oriented fracture zones and forms a major hydraulic connection between two major parts of the aquifer. Furthermore, the conductive fracture zones are conduits which connect the shallow glacifluvial aquifer system to deep groundwater in the bedrock. Understanding bedrock structures and buried topography is critical for successful groundwater modelling in crystalline, fractured bedrock.